(untitled) (KULT_online, 2014)
In this book-length discussion, James Underhill aims at exploring the connection between metaphors, ideologies, and language. He provides both a profound discussion of a number of major contributions to the field of metaphor theory and cognitive linguistics from Aristotle to George Lakoff and Paul Ricœur and, in the second part, an analysis of the significant impact metaphor has on the creation of worldviews. For exemplification, Underhill surveys the manner of speaking of the Czech communist regime during the Cold War, German rhetoric in Nazi Germany and, finally, the relationship of English as a global language to other languages, especially French.